Interleukin‐4RA gene polymorphism is associated with oral mucous membrane pemphigoid. (5th April 2013) - Carrozzo, M; Dametto, E; Fasano, ME; Broccoletti, R; Carbone, M; Rendine, S; Amoroso, A
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to analyse whether the polymorphisms of several pro‐ and anti‐inflammatory cytokines may influence the susceptibility to predominantly oral Mucous membrane pemphigoid (MMP) in a Northern Italian population. Material and Methods DNA was obtained from 41 MMP patients (29 with exclusively oral pemphigoid [OP]) and 140 unrelated bone marrow donors. Thirteen cytokine genes with 22 single‐nucleotide polymorphisms (SNP) were studied by a sequence‐specific PCR assay. Results There was no significant difference between the patients taken together and healthy controls for any cytokine gene polymorphism studied. However, the allele A of the IL‐4 receptor A (IL‐4RA) was significantly more frequent in OP than controls (P < 0.05), causing an increased frequency of genotype A/A in OP patients (89.7 vs 67.9, odds ratio: 4.11, 95% confidence intervals 1.18–14.28, P = 0.023, Pc = 0.046). Conclusion IL‐4RA‐1902 A/A genotype has been associated with a reduced response to IL‐4 and has been found in 90% OP patient. Giving the supposed importance of IL‐4 in MMP fibrotic process, our results can partially explain the low likelihood of scarring in OP patients.